2011
DOI: 10.1002/mnfr.201100377
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic effects and intestinal fermentation of cereal arabinoxylans and arabinoxylan oligosaccharides in rats depend strongly on their structural properties and joint presence

Abstract: The prebiotic potential and fermentation characteristics of cereal AX depend strongly on their structural properties and joint presence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 37 publications
6
79
0
2
Order By: Relevance
“…However, with 5% BHH supplementation, the fecal color became black or dark-brown, and the pH changed slightly to 8.0 _ 8.4. These changes in pH and color in both experiments using young and aged mice were almost the same as those observed in previous reports (Vardakou et al, 2007;Damen et al, 2011) of wheat arabinoxylans. The report noted that pH decreases upon feeding arabinoxylans were caused by the production of short-chain fatty acids, such as acetate, propionate or butyrate, and the promotion of specific bacterial growth.…”
Section: Comparison Of Fecal Ph Colour and Organic Acid Contents Betsupporting
confidence: 91%
“…However, with 5% BHH supplementation, the fecal color became black or dark-brown, and the pH changed slightly to 8.0 _ 8.4. These changes in pH and color in both experiments using young and aged mice were almost the same as those observed in previous reports (Vardakou et al, 2007;Damen et al, 2011) of wheat arabinoxylans. The report noted that pH decreases upon feeding arabinoxylans were caused by the production of short-chain fatty acids, such as acetate, propionate or butyrate, and the promotion of specific bacterial growth.…”
Section: Comparison Of Fecal Ph Colour and Organic Acid Contents Betsupporting
confidence: 91%
“…AX and their hydrolysis products, AXOS, are a promising class of prebiotics, as they have the potential to stimulate bifidobacteria, as ITF do, a so-called bifidogenic effect (12,(18)(19)(20)(21)(22)(23)(24). Also, like ITF, they seem to stimulate the production of butyrate and an increase in the relative abundance of Eubacterium spp., Roseburia spp., and F. prausnitzii, a so-called butyrogenic effect (12,18,19,21,(25)(26)(27)(28)(29).Although the bifidogenic and butyrogenic effects of AX and AXOS are considered to be beneficial for human health, their overall underlying mechanisms and microbial backgrounds are still largely unknown. It is, however, probable that cross-feeding mechanisms like those that take place with ITF occur, in which …”
mentioning
confidence: 99%
“…longum NCC2705 demonstrates the adaptation of bifidobacterial strains to these substrates important for human health (11). Further, it has been shown that the bifidogenic effect impacts indirectly other genera as well, in particular propionateand butyrate-producing colon bacteria, possibly through crossfeeding (4,10,12).…”
mentioning
confidence: 99%